Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

4(2x-1) - 2= 6 + 4 (x+7)

Sagot :

We have the following equation given:

[tex]4(2x-1)-2=6+4(x+7)[/tex]

We can start distributing the terms in the equation and we got:

[tex]8x-4-2=6+4x+28[/tex]

8x-4-2=6+4x+28

Now we can simplify:

[tex]8x-6=4x+34[/tex]

8x-6=4x+34

We can subtract in both sides of the equation 4x and we got:

[tex]4x-6=34[/tex]

4x-6=34

And now we can add in both sides 6 and we got:

[tex]4x=40[/tex]

4x=40

And finally dividing both sides by 4 we got:

[tex]x=\frac{40}{4}=10[/tex]

x=40/4=10

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.